Combined Effects of Extremely High Frequency Electromagnetic Field and Antibiotics on Enterococcus Hirae Growth and Survival - V. A. Ohanyan (ՀՀ ԳԱԱ հրատ.)
Combined effects of extremely high frequency electromagnetic field and antibiotics on Enterococcus hirae ATCC 9790 bacterial growth and survival were investigated using 51.8 GHz and 53 GHz frequencies in combination with two commonly used antibiotics: ampicillin and dalacin. Results revealed that, despite bacterial type and membrane structure and properties, the combined effect, especially with 53 GHz and dalacin, suppresses bacterial growth and decreases their survival. Совокупное воздействие электромагнитного поля сверхвысоких частот и антибиотиков на рост и выживаемость Enterococcus hirae ATCC 9790 исследовано с использованием частот 51.8 и 53 ГГц и двух часто применяемых антибиотиков: ампициллина и далацина. Показано, что, независимо от типа бактерий и структуры и свойств бактериальной мембраны, комбинированный эффект, в особенности 53 ГГц и далацина, сильнее подавляет рост бактерий и снижает их выживаемость. Ուսումնասիրվել է Enterococcus hirae ATCC9790 բակտերիայի աճի և գոյատևման վրա գերբարձր հաճախության էլեկտրամագնիսական դաշտի և հակաբիոտիկների ներգործության համատեղ ազդեցությունը` օգտագործելով 51.8 և 53 ԳՀց հաճախություններ ու երկու հաճախ օգտագործվող հակաբիոտիկներ` ամպիցիլին և դալացին: Արդյունքները ցույց տվեցին, որ անկախ բակտերիաների տիպից ու թաղանթի կառուցվածքից ու հատկություններից, համակցված ներգործությունը հատկապես 53 ԳՀց և դալացինը ճնշում է բակտերիաների աճը և նվազեցնում նրանց կենսունակությունը:
Keywords: Physics; Cell Biology; Science